The role of visual preferences in architecture views - Amini, Ali Akbar; Adibzadeh, Bahman (Journal of Architecture and Urbanism, 2020)
Since the biggest part of the human relationship with environments occurs through visual sense, the interests and wills of humans in seeing environment and architecture are important. In fact, these interests give personal or individual aspects of architecture. The role of these visual interests and mental judgments of architecture audience is very important, such that architecture has become a function of the visual preferences of the audience. Therefore, realizing these preferences is important to form architecture and ignoring them results in not providing the desired architecture condition for the audience or the required motivations for producing useful mental images to meet the basic needs of the audience. Accordingly, this study addresses the role of visual preferences in the formation of environment architecture? And which factors in this environment affect this concept? Thus, this study aims to describe the visual preferences paradigm in architecture in order to examine its different aspects in relation to human and environmental behaviors and determine the effective factors, so This study was conducted using Bourdieu’s “distinction theory” and the nature of sensory judgment with the help of field studies and descriptive analysis a number of audiences of 62 different residential environments. As a result of this research, natural, memorable, evocative environments along with the combination of open and closed spaces have shown the most visual preferences of the person towards architecture that the mental images of the person with cultural roots have been very effective in judging architecture views.